HUBUNGAN ANTARA KECANDUAN SMARTPHONE DENGAN PSYCHOLOGICAL WELL-BEING PADA REMAJA KELAS XI DI SMAN 8 KOTA JAMBI - Alma Aura Febia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Adolescence is a transitional phase marked by emotional fluctuations and a search for identity, making individuals highly vulnerable to environmental influences, including smartphone technology. This research is motivated by the increasing trend of smartphone addiction among adolescents, which is suspected of impacting their psychological well-being. At SMAN 8 Jambi City, despite school regulations, many eleventh-grade students show signs of addiction, such as decreased academic focus and social interaction disturbances like phubbing. The purpose of this study is to determine the relationship between smartphone addiction and psychological well-being among eleventh-grade students at SMAN 8 Jambi City. The research methodology employs a quantitative approach with a correlational design. Data were collected through psychological scales and analyzed using statistical techniques. Based on the preliminary study and literature review, it is indicated that excessive smartphone use correlates with a decline in psychological well-being, including aspects of personal growth and social relations. The results of this study are expected to provide a basis for guidance and counseling teachers to develop comprehensive interventions in managing technology use to enhance students' quality of life and academic achievement.